MOTIVASI KERJA PERAWAT PERIOPERATIF BERDASARKAN TEORI Mc-Clelland HUBUNGANNYA DENGAN PENERAPAN 6 SASARAN KESELAMATAN PASIEN : PERIOPERATIVE NURSES' WORK MOTIVATION BASED ON McClelland'S THEORY AND ITS RELATIONSHIP WITH THE IMPLEMENTATION OF THE SIX PATIENT SAFETY GOALS - Nahla Esella Septiana Dasa; Tri Anjaswarni; Imam Subekti; Naya Ernawati (Politeknik Kesehatan Kemenkes RI Jakarta I, 2026)
Nurses' motivation in working is for achievement, power, and affiliation, in addition to financial needs. Nurses' motivation for patient safety has not been evaluated and is still inconsistently implemented. During surgical procedures, patients still use personal items that pose a risk of infection, cotton or gauze is left behind, and many other post-surgical incidents occur due to negligence. Therefore, the consistency of nurses' motivation, particularly in maintaining patient safety during surgical procedures, needs to be evaluated. This study aims to analyze the relationship between perioperative nurses' work motivation based on McClelland's theory and the implementation of 6 patient safety goals at Karsa Husada Batu Regional Hospital. This study used a correlational design with a cross-sectional approach. The study sample was all 37 perioperative nurses (Operating Room and Edelweiss Room A) at Karsa Husada Batu Regional Hospital. Data analysis used the Spearman Rank correlation test. The results of the statistical test showed a significant relationship between perioperative nurses' work motivation and the implementation of 6 patient safety goals (p-value = 0.001; r = 0.541). The relationship is classified as moderate with a positive direction, meaning that the higher the nurse's work motivation, the better the implementation of the 6 patient safety goals. The contribution of research in the field of nursing, particularly in the perioperative area, is to provide information that the implementation of the 6 patient safety goals requires high motivation for nurses to be consistent in their implementation. The work motivation of perioperative nurses must be continuously improved, one way of which is by referring to McClelland's theory. High awareness is needed in monitoring patient safety and it is necessary to improve the competence of nursing staff in a program to implement good practices through training and ensuring nurses' compliance with patient safety standards.